Research Progress on the Isolation, Purification, Structural Characteristics and Biological Activity Mechanism of Pleurotus citrinopileatus Polysaccharides - Zixu Liu; Honglei Wang (Molecules, 2025)
Pleurotus citrinopileatus, a valuable edible fungus characterized by its distinctive light yellow coloration and saprophytic growth on elm wood, has garnered increasing scientific interest due to its diverse bioactive constituents. Among these, polysaccharides derived from P. citrinopileatus (PCPs) have received the most extensive research attention. This review summarizes recent advances in the chemical structure and biological activities of PCPs. Structurally, PCPs are primarily composed of repeating units such as →3)-α-D-Glcp-(1→ and →6)-α-D-Galp-(1→. Functionally, PCPs exhibit a range of bioactivities, including immunomodulatory, hypoglycemic, and antitumor effects. Furthermore, the underlying mechanisms associated with these biological activities are also explored. This review aims to provide a comprehensive reference for future studies and facilitate the development and application of PCPs as potential functional food ingredients or therapeutic agents.